IRF-5 Expression in Myeloid Cells Is Required for Splenomegaly in L. donovani Infected Mice - Mai, Linh Thuy; Smans, Mélina; Silva-Barrios, Sasha; Fabié, Aymeric; Stäger, Simona (Frontiers in Immunology, 2020)
Persistent Leishmania donovani infection is characterized by chronic inflammation, immune suppression, and splenomegaly. We have previously reported that the transcription factor interferon regulatory factor 5 (IRF-5) is largely responsible for inducing the inflammatory response and maintaining protective Th1 cells following L. donovani inoculation in mice. However, the cellular source responsible for these effects is yet unknown. In this study, we investigated the role of IRF-5 in myeloid cells during experimental visceral leishmaniasis (VL). First, we show that the LysM-Cre mouse model is not suited for investigating gene expression in splenic myeloid cells during experimental VL. Using the Cd11c-Cre mouse model, we demonstrate that Irf5 expression in CD11c+ cells (monocytes, dendritic cells, activated macrophages) is essential for inducing splenomegaly and for recruiting myeloid cells to the spleen, but it is not required for the development or maintenance of parasite-specific IFNγ-producing CD4 T cells. CD11c-specific Irf5−/− mice are more resistant to L. donovani infection, suggesting that the induction of splenomegaly is detrimental to the host.